The Ethnic Distribution of the Enslaved Population of Southern Mozambique following the Mfecane: An Analysis of the Registers of Slaves and Libertos of Lourenço Marques (Delagoa Bay), 1856-1874 - Domingues da Silva, Daniel B. (Journal of southern African studies, 2025)
The Nguni upheavals of the early 19th century, commonly known as the Mfecane, not only changed the political landscape of southern Mozambique but also shaped the ethnic distribution of the enslaved population living in that region. While the causes of the Mfecane have been discussed in depth, little attention has been paid to the impact of the Mfecane on the history of slavery and the slave trade in southern Mozambique. This article seeks to bridge that gap by providing an analysis of the registers of slaves and freed persons made by Portuguese colonial authorities in the district of Lourenço Marques, located in the Delagoa Bay area (nowadays Maputo Bay), between 1856 and 1874. It shows that the Mfecane significantly changed the ethnic make-up of the enslaved population of southern Mozambique by increasing the number of enslaved Nguni in the region, particularly Gaza Nguni. Furthermore, it argues that the enslaved Nguni included not only refugees of the upheavals in their homeland but also victims of the Gaza civil war in the years immediately following the Mfecane.